Analisis Tindak Tutur Lokusi pada Konten Review Handphone dalam Kanal YouTube GadgetIn - Tri Wulaningsih; Norma Hidayanti; Ni’matul Maula Fitriani; Sabrina Defti Maharani; Jihan Aina Nabila; Asep Purwo Yudi Utomo; Anggit Wicaksono (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
This article aims to analyze the locutionary speech acts used in cellphone review content on the YouTube channel "Gadgetin". Locutionary speech acts are an important aspect in language and communication analysis. Locutionary speech acts can provide in-depth insight into how content creators communicate with audiences in the context of technology product reviews. This research uses a qualitative approach by collecting data from a number of cellphone review videos published on the "Gadgetin" channel. Data were analyzed using the speech act theory framework of Austin (1962) and Searle (1969) to identify the speech acts used in the video. The results of the analysis show that there are significant differences in the use of locutionary speech acts in cellphone review content. Based on the data collected, this research classifies locutionary speech acts into several types, including statements of fact about technical specifications, opinions about product quality, audience requests, and others. Apart from that, this article also discusses how the use of slogans affects communication between content creators and their audiences. The research results show that the effective use of locutionary speech acts can increase audience participation and support communication goals in the context of motion review. This research contributes significantly to understanding the use of language in technology product review content on the YouTube platform. The results of this cellphone review analysis can be a benchmark for YouTube content producers and researchers to understand the dynamics of communication in an ever-evolving digital context.